Associative and Propositional Process in Evaluation An Integrative Review of Implicit and Explicit Attitude Change. [article]. - Gawronski, Bertram
A central theme in recent research on attitudes is the distinction between deliverate "explicit" attitudes and automatic, "implicit" attitudes. The present article provides an integrative review of the available evidence on implicit and explicit attitude change that is guided by a distinction between associative and propositional processes. Whereas associative processes are characterized by mere activation independent of subjective truth or falsity, propositional reasoning is concerned with the validation of evaluations and beliefs. The proposed associative-propositional evaluation (APE) model makes specific assumptions about the mutual interplay of the 2 processes, implying several mechanisms that lead a symmetric or asymmetric changes in implicit and explicit attitudes. The model integrates a broad range of empirical evidence and implies several new predictions for implicit and explicit attitude change. -- (from the author)
Keywords: Attitude change; Cognitve consistency; Dual-process models; Evaluative conditioning; Implicit measures